Are psychogenic nonepileptic seizures genetically determined? It is time to explore!. (November 2015) - Asadi-Pooya, Ali A.
Highlights: Pathophysiology of PNES is still poorly understood. An association of PNES with organic brain dysfunction appears to be likely. The most obvious genetically determined risk factor for PNES is gender. Genetic analysis could potentially lead to improved diagnosis and treatment of PNES.